Dramatically improved left ventricular function after biventricular pacemaker implantation--a case report - Bulava, Alan; Lukl, Jan; Skvarilová, Marcela; Marek, Dan (European journal of heart failure, 2005)
A case study of a patient suffering from severe chronic congestive heart failure resulting from ischemic cardiomyopathy in whom a biventricular (BiV) pacing system was implanted is reported. After a 1-year follow-up, left ventricular (LV) ejection fraction improved dramatically from an initial 15% to 60%, left ventricular end-diastolic diameter decreased, as did left atrial dimension. Tissue Doppler data and acute hemodynamic measurements taken during the biventricular pacemaker implantation procedure are presented. The case represents an exceptional example of left ventricular reverse remodeling with practically normalized left ventricular function after 1 year of synchronized pacing.
Keywords: Heart Failure; Pacemaker, Artificial; Cardiac Pacing, Artificial; Stroke Volume; kardiostimulátor; funkce levé komory srdeční; lidé; srdeční selhání; senioři; Female; kardiostimulace umělá; Aged; Treatment Outcome; tepový objem; výsledek terapie; ženské pohlaví; Ventricular Function, Left; Humans